Karakteristik Sedimen Sungai Matangnga (Hulu) dan Sungai Maloso (Hilir) Kabupaten Polewali Mandar Berdasarkan Parameter Statistik Ukuran Butir - Suryani, Herni; Jamal, Elvira; Yusman (Universitas Sulawesi Barat, 2025)
This study investigates the sediment characteristics of the Matangnga River (upstream) and Maloso River (downstream) in Polewali Mandar Regency based on grain size statistical parameters to understand sediment transport dynamics and depositional mechanisms. Eight sediment samples were analyzed using granulometric methods and statistical approaches by Folk & Ward (1957), combined with log-probability curve interpretation based on Visher (1969). Results indicate that upstream sediments are predominantly coarse-grained with poor to moderate sorting and exhibit multimodal grain size distributions. In contrast, downstream sediments are finer, better sorted, and show unimodal distributions, indicating dominant suspension deposition. Log-probability analysis identified the presence of three major transport mechanisms (traction, saltation, suspension), varying between observation stations. This study demonstrates that integrating grain size statistics and log-probability curves effectively interprets fluvial sedimentation dynamics and depositional environment transitions.